Aluminium(III), Fe(II) complexes and dyeing properties of apigenin(5,7,4'-trihydroxy flavone) - (:unkn) unknown (Walter de Gruyter GmbH, 2010)
Apigenin and its metal complexes are used extensively in chemistry, biology and dye industry. In this study, the interactions of flavonoids with metal ions and dyeing properties of these complexes are studied and the complexes of apigenin with aluminium and iron are examined by spectrophotometric and Potentiometrie methods. The evaluated protonation constants of the apigenin were found: logK1= 8.21 and logK2= 2.83 at the 25°C. Logarithms of the stability constants were found: for Aluminium complex : logK1= 8.24, logK2 = 7.46, and logK3= 7.04 and for Iron complex : logK1= 7.52, logK2=5.80, and logK 3= 5.00 at the 25°C. The stoichiometry of metal-apigenin complexes are given 1:3 (metal: apigenin ratio) 100 both Al(III) and Fe(II) from the results. According to our works; it can be said that Al(III) -apigenin and Fe(II)- apigenin complexes are formed the dyeing process and this increases the lightfastness of the dyeing.
Keywords: Aluminium; Apigenin; Dyeing; Iron; Potentiometry; Spectrophotometry; Stability constant